2018
DOI: 10.1371/journal.pone.0190730
|View full text |Cite
|
Sign up to set email alerts
|

Long-term dietary replacement of fishmeal and fish oil in diets for rainbow trout (Oncorhynchus mykiss): Effects on growth, whole body fatty acids and intestinal and hepatic gene expression

Abstract: The effects of replacing fishmeal and fish oil with a plant-based diet were studied in juvenile (10g) and ongrowing (250-350g) rainbow trout from first-feeding. Feed-related differences in the intestinal and hepatic transcriptome were examined in juveniles after 7 months of feeding at 7°C. Based on microarray results obtained for juveniles, the expression of selected genes related to lipid, cholesterol and energy metabolisms, was assessed by RT-qPCR in ongrowing trout after 6 additional months of feeding at 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(77 citation statements)
references
References 62 publications
11
63
0
1
Order By: Relevance
“…After 13 months of feeding without fish meal and fish oil, the mean body mass of the “plant” group P was significantly lower than that of the other two groups (Lazzarotto et al., ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…After 13 months of feeding without fish meal and fish oil, the mean body mass of the “plant” group P was significantly lower than that of the other two groups (Lazzarotto et al., ).…”
Section: Resultsmentioning
confidence: 98%
“…At the end of this second period of feeding, the fish were fasted for 48 hr before sampling as described previously (Lazzarotto et al., ). Five trout were randomly sampled from each tank (15 fish per experimental group), weighed and euthanized, before collecting plasma for biochemical and metabolomic analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, FM replacements in feedstuffs are known to affect the metabolic response at different levels, including gene expression. Lazzarotto, Médale, Larroquet, and Corraze () observed that hepatic genes involved in long‐chain polyunsaturated fatty acids bioconversion and cholesterol biosynthesis were up‐regulated when fish meal was completely replaced by a plant‐based diet. Although our results suggest stimulation of the lipogenic pathways in P. mesopotamicus fed with the BPPD, further studies are needed to elucidate the mechanistic pathways causing such effect.…”
Section: Discussionmentioning
confidence: 99%
“…Research continues to investigate the successful substitution of fishmeal with alternative (preferably vegetable) diets in fish feeds. Success in this research field would allow aquaculture to increase its overall fish production without threatening wild fish stocks (Lazzarotto et al , ) and help counter debates on unsustainable sources of feed ingredients.…”
Section: Constraintsmentioning
confidence: 99%